Keamanan Kernel Linux : Pendekatan Hardening dan Perlindungan terhadap Serangan Eksploitasi - Zalfa Dewi Zahrani; Novianto Andi Hardiansyah; Elkin Rilvani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Linux kernel security is a critical aspect of ensuring the integrity and stability of operating systems. Vulnerabilities like Dirty COW (CVE-2016-5195) illustrate how exploitative threats can severely impact systems, particularly those that are not regularly updated. This study analyzes the working mechanism of Dirty COW, its impact, and mitigation strategies based on Linux kernel hardening techniques, including the use of security modules like SELinux and AppArmor, as well as the Address Space Layout Randomization (ASLR) technique. Through attack simulations and mitigation evaluations, the findings emphasize the importance of regularly applying kernel patches to maintain system security. This study aims to provide practical guidance for enhancing Linux kernel resilience against exploitation attacks.